(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
The growing energy demand in the world, as well as the current geopolitical situation, require countries to additional investments in the exploration and production of hydrocarbons from their own sources. This means that companies must develop new fields which have remained undeveloped until now mostly because extremely harsh environment where they are located (deep sea, high temperature, high pressure, heavy oils, etc.). The development of these new fields requires the development and adoption of new technology, among other things, and the development of a temperature-stable drilling fluid system able to fulfil all tasks according to the new technical challenges. Except for the technological challenges, there are also growing concerns related to the influence of the drilling operation on the environment. All of the above encourage the industry to develop new, inexpensive, and environmentally friendly additives which will be able to satisfy all technical and technological requirements and challenges of modern drilling. In the last few years, there has been a growing trend of laboratory research that includes different types of biodegradable waste as a potential additive that can achieve useful properties in mud. In this paper, the influence of mandarin peel powder on the filtration properties of mud after the aging process at elevated temperatures is examined. This eco-friendly additive was added to water-based muds in concentrations of 1% and 2% by volume of water. Laboratory research have shown stable filtration properties of the water-based mud containing mandarin peel powder even after exposing the mud to temperatures higher than 130 °C.